Anionic retention aid and retention improvement method using same
A water-in-oil emulsion of anionic water-soluble polymer addresses the issue of floc breakdown under high shear in papermaking by improving retention and yield, ensuring effective paper production even at increased speeds.
Patent Information
- Application Number
- JP2020131334
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-03
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-08-03
AI Technical Summary
Existing papermaking processes face challenges in maintaining retention of papermaking raw materials under high shear conditions, leading to reduced yield and quality due to the breakdown of flocs formed by anionic polymers, especially at increased papermaking speeds.
A water-in-oil emulsion of anionic water-soluble polymer with specific monomer composition is added before papermaking to enhance retention, featuring a charge inclusion rate and shear resistance, allowing for effective retention even under high shear conditions.
The emulsion provides improved yield and paper quality by maintaining floc integrity despite high shear forces, enhancing retention and productivity in papermaking processes.
Smart Images

Figure 0007619554000001 
Figure 0007619554000002 
Figure 0007619554000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a retention aid for use in the papermaking process and a method for improving the retention of papermaking raw materials using the same, and more particularly to a method for improving the retention of papermaking raw materials on a wire by using an anionic retention aid in the papermaking process. [Background technology]
[0002] In the papermaking process of coated base paper, PPC paper, wood-free paper, paperboard, and newsprint, retention aids are used to improve the retention rate of raw pulp, fine fibers, fillers, papermaking chemicals, etc. on the wire, or drainage aids (or yield and drainage aids) that emphasize the function of improving drainage as well as retention are used. Generally, polyacrylamide (PAM) polymers are widely used as retention aids, but due to the diversification of papermaking conditions in recent years, effective retention aids and retention systems vary. A decrease in the retention rate of papermaking raw materials on the wire not only reduces productivity, but also reduces the retention of papermaking chemicals such as fillers, strength agents, and sizing agents contained in the papermaking raw materials, which is one of the factors that leads to a decrease in the quality of paper products. Cationic PAMs or amphoteric PAMs are the mainstream, but there are also papermaking conditions in which anionic PAMs are effective. In general, when applying anionic PAM, it is often added after passing through the screen.If it is added before passing through the screen (at the inlet) or before or after the fan pump upstream of the screen in the papermaking process, shear force is applied, destroying the flocs formed by the retention aid, reducing the retention effect. In addition, in order to improve productivity in paper mills, the wire papermaking speed is being increased to over 800 m / min, and even over 1000 m / min. As the papermaking speed increases, the shear force applied to the papermaking raw material increases, making the formed flocs more likely to break, and reducing the retention effect. In general, the retention effect can be improved by increasing the molecular weight of the anionic PAM. For example, Patent Document 1 discloses a retention agent containing an anionic polymeric compound with a viscosity average molecular weight of more than 35 million and a low charge density. However, adding a high molecular weight retention agent has a large effect on the formation, so the addition rate is limited. In addition, when a shear force is applied, the flocs are easily broken and the formed flocs cannot be maintained. Therefore, various methods of changing the structure of anionic PAM have been attempted to suppress the influence on the formation and to give shear resistance. Patent Document 2 describes that when a crosslinked anionic water-soluble polymer is used as a retention aid, the raw flocs of papermaking material do not become huge but become small and compact, and are resistant to shear. Patent Document 3 discloses crosslinked anionic or amphoteric organic polymer particles, and Patent Document 4 discloses a water-in-water polymer dispersion containing a crosslinked anionic polymer, and suggests their use for the purpose of improving retention. However, although the influence on paper quality can be relatively suppressed by using these polymers with modified structures, a satisfactory retention effect is not necessarily obtained. In addition, these anionic polymers are often used in combination with cationic or amphoteric PAM, and are mainly added to the screen outlet. When added before or after the fan pump or at the screen inlet, shear force is applied and the distance to the papermaking machine is long, so the formed flocs are easily broken during that time. In addition, in the case of high-speed papermaking, the shear force is also strong, so the flocs break, resulting in a decrease in retention effect. Therefore, there is a demand for the development of an anionic retention aid that provides a high retention effect even under papermaking conditions with high shear.
[0003] [Patent Document 1] International Publication No. 2015 / 053349 [Patent Document 2] JP 2016-104433 A [Patent Document 3] Japanese Patent Application Publication No. 4-226102 [Patent Document 4] Special Publication No. 2013-502502 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention relates to a retention aid for use in the papermaking process and a method for improving the retention of papermaking raw materials using the same, and has an objective of providing an anionic retention aid that can be applied under papermaking conditions involving high shear and a method for improving the retention of papermaking raw materials using the same. [Means for solving the problem]
[0005] As a result of intensive research conducted to solve the above problems, it has been found that the retention rate of papermaking raw materials can be improved by adding a water-in-oil emulsion of an anionic water-soluble polymer having specific composition and physical properties as a retention aid to the papermaking raw materials before papermaking. Effect of the Invention
[0006] By adding the water-in-oil emulsion of an anionic water-soluble polymer of the present invention as a retention aid to the papermaking raw material before papermaking, a higher retention rate can be obtained under papermaking conditions involving high shear, thereby achieving improved productivity and improved paper quality. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The water-in-oil emulsion of an anionic water-soluble polymer in the present invention is produced by emulsifying an aqueous monomer mixture solution containing 5 to 80 mol % of a monomer represented by the following general formula (1) and 20 to 95 mol % of a nonionic water-soluble monomer with a surfactant so that a water-immiscible organic liquid forms the continuous phase and the aqueous monomer mixture solution forms the dispersed phase, polymerizing the solution, and then adding a phase inversion agent. TIFF0007619554000001.tif2660 General formula (1) R1 represents hydrogen, a methyl group or a carboxymethyl group, Q represents SO3, C6H4SO3, CONHC(CH3)2CH2SO3, C6H4COO or COO, R2 represents hydrogen or COOY2, and Y1 or Y2 represents hydrogen or a cation.
[0008] The anionic monomer used in producing the water-in-oil emulsion of the anionic water-soluble polymer in the present invention, i.e., the monomer represented by the general formula (1), is in the range of 5 to 80 mol %. If it is less than 5 mol %, a large retention effect due to the anionic group of the anionic water-soluble polymer cannot be obtained, and if it is more than 80 mol %, it becomes difficult to obtain a high molecular weight polymer. The range of 10 to 70 mol % is preferable.
[0009] Examples of the anionic monomer represented by the general formula (1) include vinylsulfonic acid, vinylbenzenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, methacrylic acid, acrylic acid, itaconic acid, maleic acid, phthalic acid, p-carboxystyrene acid, and salts thereof. Two or more of these may be used in combination.
[0010] Examples of the nonionic monomer used in the present invention include (meth)acrylamide, N,N'-dimethylacrylamide, acrylonitrile, (meth)acrylate-2-hydroxyethyl, diacetone acrylamide, N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, and acryloylmorpholine. Two or more of these may be combined. The molar amount of the nonionic monomer is 20 to 95 mol%, and preferably 30 to 90 mol%.
[0011] When producing the water-in-oil emulsion of the anionic water-soluble polymer of the present invention, a cationic monomer can be used within a range that does not impair the effect. The amount of the cationic monomer used is in the range of 0 to less than 10 mol %, and if it is 10 mol % or more, the effect as an anionic retention aid decreases. It is preferably less than 5 mol %.
[0012] When using cationic monomers in the present invention, the following are available. That is, quaternized products of methyl chloride or benzyl chloride such as dimethylaminoethyl (meth)acrylate and dimethylaminopropyl (meth)acrylamide. Examples include (meth)acryloyloxyethyl trimethylammonium chloride, (meth)acryloyloxy-2-hydroxypropyl trimethylammonium chloride, (meth)acryloylaminopropyl trimethylammonium chloride, (meth)acryloyloxyethyl dimethylbenzylammonium chloride, (meth)acryloyloxy-2-hydroxypropyl dimethylbenzylammonium chloride, and (meth)acryloylaminopropyl dimethylbenzylammonium chloride. Two or more of these can also be combined.
[0013] The water-in-oil emulsion of the anionic water-soluble polymer of the present invention can be produced by copolymerizing a monomer mixture containing an anionic monomer and a nonionic monomer. The polymerization is carried out by preparing an aqueous solution of a mixture of these monomers and then using a conventional water-in-oil emulsion polymerization method.
[0014] The water-in-oil emulsion can be appropriately produced according to the methods described in JP-A-55-137147, JP-A-59-130397, JP-A-10-140496, JP-A-2011-99076, etc. A monomer mixture containing an anionic monomer and a nonionic monomer is mixed with water, an oily substance consisting of a water-immiscible hydrocarbon, and at least one surfactant having an effective amount and HLB for forming a water-in-oil emulsion, and the mixture is stirred vigorously to form a water-in-oil emulsion, followed by polymerization.
[0015] In the present invention, when producing a water-in-oil emulsion of an anionic water-soluble polymer, it is preferable to add an inorganic salt since it improves the retention effect. The timing of adding the inorganic salt is in the aqueous solution in which the monomer mixture containing the anionic monomer and the nonionic monomer is mixed. Alternatively, the inorganic salt may be divided and a part of it may be added to the aqueous solution in which the monomer mixture is mixed, and the rest may be added to the water-in-oil emulsion during polymerization or after copolymerization.
[0016] The inorganic salt to be added may be a salt obtained by combining a cation such as an alkali metal ion such as sodium or potassium, an ammonium ion, or a magnesium ion with an anion such as a halide ion, a sulfate ion, a nitrate ion, or a phosphate ion. The concentration of these salts is preferably 0.5 to 10% by mass relative to the amount of the water-in-oil emulsion. If the concentration is less than 0.5% by mass, it is difficult to further improve the retention effect, and if the concentration is more than 10% by mass, it is difficult to add the inorganic salt in the manufacturing process due to the solubility of the inorganic salt, and if the concentration is more than 5% by mass, the charge encapsulation rate tends to be 15% or less, so the concentration is preferably in the range of 0.5 to 5% by mass.
[0017] Examples of oily substances made of hydrocarbons used as a dispersion medium include paraffins, mineral oils such as kerosene, light oil, and medium-weight oil, synthetic hydrocarbon oils having substantially the same ranges of boiling point, viscosity, and other properties, and mixtures thereof. The content is in the range of 20% by mass to 50% by mass, and preferably 20% by mass to 35% by mass, based on the total amount of the water-in-oil emulsion.
[0018] An example of at least one surfactant having an effective amount and HLB for forming a water-in-oil emulsion is a nonionic surfactant with an HLB of 3 to 11, and specific examples thereof include sorbitan monooleate, sorbitan monostearate, sorbitan monopalmitate, polyoxyethylene nonylphenyl ether, etc. The amount of these surfactants to be added is 0.5 to 10% by mass, preferably 1 to 5% by mass, based on the total amount of the water-in-oil emulsion.
[0019] After polymerization, a hydrophilic surfactant called a phase inversion agent is added to make the emulsion particles covered with an oil film more compatible with water and to make the water-soluble polymer inside more soluble, and then the emulsion is diluted with water for use. Examples of hydrophilic surfactants include cationic surfactants and nonionic surfactants with HLB of 9 to 15, such as polyoxyethylene polyoxypropylene alkyl ethers and polyoxyethylene alcohol ethers.
[0020] The polymerization conditions are usually appropriately determined depending on the monomers and copolymerization mol% used, and the temperature is in the range of 20 to 80°C, preferably 20 to 60°C. A radical polymerization initiator is used to start the polymerization. These initiators may be either oil-soluble or water-soluble, and polymerization can be carried out using any of azo, redox, and peroxide initiators. Examples of oil-soluble azo initiators include 2,2'-azobisisobutyronitrile, dimethyl-2,2'-azobisisobutyrate, 1,1'-azobiscyclohexanecarbonitrile, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis-2-methylpropionate, and 4,4'-azobis-(4-methoxy-2,4-dimethyl)valeronitrile.
[0021] Examples of water-soluble azo initiators include 2,2'-azobis(amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-imidazolin-2-yl)propane] dihydrochloride, 4,4'-azobis(4-cyanovaleric acid), etc. Examples of redox initiators include combinations of ammonium peroxodisulfate with sodium sulfite, sodium hydrogensulfite, trimethylamine, tetramethylethylenediamine, etc. Examples of peroxide initiators include ammonium or potassium peroxodisulfate, hydrogen peroxide, benzoyl peroxide, lauroyl peroxide, octanoyl peroxide, succinic peroxide, t-butylperoxy-2-ethylhexanoate, etc. The addition rate of the azo-based or peroxide-based initiator is 50 to 5000 ppm, preferably 100 to 500 ppm, per monomer at the start of polymerization. However, since the polymerization rate is low when these initiators are added in one go, it is preferable to add them in several portions.
[0022] In order to adjust the degree of polymerization, it is effective to use isopropyl alcohol in an amount of 0.1 to 5% by mass based on the monomer, sodium formate in an amount of 0.02 to 0.5% by mass based on the monomer, or sodium phosphinate in an amount of 0.0005 to 0.05% by mass.
[0023] The polymerization concentration of the monomer is in the range of 20 to 50% by mass, and the polymerization concentration and temperature are appropriately set depending on the monomer composition and the selection of the initiator.
[0024] The polymer structure of the anionic water-soluble polymer in the present invention is indicated by the charge-containing ratio. The charge-containing ratio used in the present invention is defined as follows. Definition (A): Charge inclusion rate (%)=(1-α / β)×100 α is the titration amount obtained by titrating a 0.0025 mass% aqueous solution of anionic water-soluble polymer adjusted to pH 10.0 with ammonia using a PCD titrator (PCD-500, AT-510) manufactured by Kyoto Electronics Manufacturing Co., Ltd., with a dropping solution: 1 / 1000N polydiallyldimethylammonium chloride aqueous solution, a dropping rate: 0.1 ml / 5 sec, and an end point judgment: 0 mV. β is the titration amount obtained by applying shear to a 0.0025 mass% aqueous solution of anionic water-soluble polymer adjusted to pH 10.0 with ammonia using an Ace Homogenizer (AM-11) manufactured by Nippon Seiki Seisakusho Co., Ltd., under conditions of 10,000 rpm and 5 minutes, and then similarly titrating the solution using a PCD titration apparatus with a dropping solution: 1 / 1000N polydiallyldimethylammonium chloride aqueous solution, a dropping rate: automatic control, and an end point judgment: 0 mV. The PCD titration apparatus is not limited to the above-mentioned apparatus as long as it can perform similar measurements. However, in order to specify the numerical values, the experimental error of the charge encapsulation rate of the same ionic polymer measured under the above-mentioned conditions with the above-mentioned apparatus must be within ±0.5%.
[0025] The titration amount α value refers to the procedure of dropping an aqueous solution of polydiallyldimethylammonium chloride having an opposite charge onto a sample anionic water-soluble polymer, thereby causing an ionic electrostatic reaction with the ionic groups present on the "surface" (particulate surface) of the water-in-oil emulsion of the anionic water-soluble polymer. The titration amount β value is considered to correspond to the theoretical charge amount calculated from the chemical composition of the water-soluble polymer. In other words, since there is a large amount of opposite charge that appears due to shearing with respect to the water-soluble polymer, it is considered that an electrostatic neutralization reaction takes place not only on the surface charge but also on the internal charge. If the degree of crosslinking is high, α becomes smaller than β, the (1-α / β) value becomes larger, and the charge encapsulation rate becomes large (i.e., the degree of crosslinking becomes high).
[0026] In other words, it can be said that a water-soluble polymer with a high charge encapsulation rate is a water-soluble polymer with a high degree of cross-linking, and a water-soluble polymer with a low charge encapsulation rate is a water-soluble polymer with a low degree of cross-linking. The reason for this is explained as follows. In a dilute solution, the molecules of a straight-chain water-soluble polymer are almost "extended". On the other hand, a cross-linked water-soluble polymer has a rounded particulate shape in the solution, and the ionic groups present inside the particulates are unlikely to appear on the outside, and it is thought that the reaction with the opposite charge also occurs slowly.
[0027] In the case of normal linear polymers or cross-linked polymers, increasing the molecular weight causes the polymer to shrink or become entangled with other polymers, reducing the charge on the polymer surface and suppressing the charge neutralization action. As a result, when used as a retention aid, the retention effect may decrease. This phenomenon is unlikely to occur when the charge inclusion rate is 15% or less, but when it exceeds 15%, the branched structure progresses and the branching progresses to the point of intermolecular cross-linking, causing strong entanglement, reducing the surface charge of the polymer, which tends to decrease the retention effect. However, in the anionic water-soluble polymer of the present invention, even if the charge encapsulation rate exceeds 15%, by optimizing the type and amount of the polymerization initiator and chain transfer agent, and the polymerization conditions, a certain range of charge encapsulation rate and high molecular weight can be achieved, resulting in a high retention effect under papermaking conditions involving high shear. The charge encapsulation rate is preferably more than 15.0% and 30.0% or less, more preferably 17.0% or more and 30.0% or less, and even more preferably 20.0% or more and 30.0% or less. When the charge encapsulation rate is within this range, when a high shear load is applied, the charge present inside gradually appears on the outside, and the charge neutralization effect works effectively, so that shear resistance is more expressed. If the charge encapsulation rate exceeds 30.0%, it is difficult to obtain a high molecular weight, so this is not preferable. In addition, the water-in-oil emulsion of an anionic water-soluble polymer in the present invention is preferably added with an inorganic salt because the addition of an inorganic salt produces steric hindrance and charge repulsion, which serves to adjust the entanglement between the polymers, thereby enabling the emulsion to be more effective.
[0028] In the water-in-oil emulsion of the anionic water-soluble polymer of the present invention, a crosslinkable monomer may be used as a structure modifier during or after polymerization. When used, the amount is in the range of 0.0001 to 0.1% by mass relative to the total amount of monomers. Examples of crosslinkable monomers include N,N'-methylenebis(meth)acrylamide, triallylamine, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, polyethylene glycol di(meth)acrylate, N-vinyl(meth)acrylamide, N-methylallylacrylamide, glycidyl acrylate, polyethylene glycol diglycidyl ether, acrolein, glyoxal, vinyltrimethoxysilane, etc., and among these, N,N'-methylenebis(meth)acrylamide is preferred.
[0029] The water-in-oil emulsion of an anionic water-soluble polymer in the present invention needs a high molecular weight to obtain a high coagulation force. When the molecular weight is expressed in terms of intrinsic viscosity, the intrinsic viscosity of the water-soluble polymer constituting the water-in-oil emulsion in a 4% by mass saline solution at 0.5% by mass measured at 25°C is 15 to 30 dl / g, preferably 17 to 30 dl / g, and more preferably 20 to 30 dl / g. If the intrinsic viscosity is lower than 15 dl / g, the effect of improving the retention rate is significantly reduced, and if it is higher than 30 dl / g, the quality of the paper, especially the texture, tends to decrease, which is not preferable. The weight average molecular weight measured by the intrinsic viscosity method is preferably within the range of 10 to 30 million. In addition, the viscosity measured at 25°C when the polymer is dissolved in 4% by mass saline to a concentration of 0.5% by mass (viscosity of 0.5% by mass saline solution) can also be used as an index of molecular weight, and the viscosity of the 0.5% by mass saline solution is preferably in the range of 150 to 350 mPa·s.
[0030] The retention aid of the present invention, which is a water-in-oil emulsion of an anionic water-soluble polymer, is added to the papermaking raw material before papermaking. In the papermaking process, the papermaking raw material is usually transferred from the upstream with a pulp dry solids concentration of 2.0% by mass or more, and is diluted with white water or fresh water just before the papermaking machine to a papermaking raw material with a pulp dry solids concentration of less than 2.0% by mass. Generally, it is diluted to 0.5 to 1.5% by mass, and these are called inlet raw materials or headbox raw materials. A retention aid is added to these raw materials (hereinafter referred to as inlet raw materials) and paper is made. The retention aid of the present invention is also applied to the inlet raw material.
[0031] The location of addition of the water-in-oil emulsion of an anionic water-soluble polymer in the papermaking process in the present invention is before or after the fan pump, which is a shearing process, or before passing through a screen. If a conventional anionic retention aid is added before passing through a screen or before or after the fan pump, which is upstream of the screen in the papermaking process, shear force is applied, and the effect is reduced. However, the water-in-oil emulsion of an anionic water-soluble polymer in the present invention has excellent shear resistance, so it can be effectively added to the screen inlet (before passing through) or before or after the fan pump, which is upstream of the screen inlet in the papermaking process, and exhibits a retention effect. It may also be added in portions. The papermaking raw material before papermaking, to which the water-in-oil emulsion of an anionic water-soluble polymer has been added, has excellent shear resistance even when passing through the fan pump or screen shearing process, and as a result, a higher retention effect can be obtained than with conventional anionic PAM.
[0032] On the other hand, in order to improve productivity in paper factories, papermaking speeds are increasing, reaching speeds of 800 m / min or more, and sometimes even exceeding 1000 m / min. As the papermaking speed increases, the shear force applied to the papermaking raw material increases, making the flocs formed by the addition of a retention aid more likely to break. This tendency is particularly pronounced at speeds of 800 m / min or more, and a retention aid that can maintain the flocs even at high shear is required, and the performance of the water-in-oil emulsion of an anionic water-soluble polymer of the present invention is more effectively achieved at high-speed papermaking. A papermaking speed of 800 m / min or more is preferred, and 1000 m / min or more is more preferred. As long as the effects of the present invention can be obtained, there is no particular upper limit to the papermaking speed.
[0033] The types of paper for which the retention aid comprising the water-in-oil emulsion of an anionic water-soluble polymer of the present invention can be used include newsprint, fine printing paper, medium printing paper, gravure printing paper, PPC paper, coated base paper, lightly coated paper, wrapping paper, liner and core base paper board, etc. It is effective for papermaking raw materials with a relatively low anion content, i.e., a relatively low cationic demand. Specifically, the cationic demand is 0.0 If the anionic water-in-oil emulsion of the present invention is 3 meq / L or less, it is effective. It is preferably 0.02 meq / L or less, and more preferably 0.01 meq / L or less. It is also effective if the papermaking raw material shows cationicity (=anionic demand). It is effective when applied to paperboard such as liner and core raw paper that contains a relatively high content of paper strength agents such as cationic or amphoteric starch or aluminum sulfate. The cationic demand is expressed as a value (meq / L) measured by using a commercially available particle charge meter (such as PCD-05 model by Mutec Co., Ltd.) for the filtrate of Whatman No. 41 filter paper. The water-in-oil emulsion of the anionic water-soluble polymer in the present invention is used by diluting and dissolving it in water to 0.01 to 1.0% by mass. The water to be used for dissolution may be distilled water, ion-exchanged water, tap water, industrial water, or the like. These may be mixed. The diluted solution may be further diluted a second time or a third time. The addition rate of the water-in-oil emulsion of an anionic water-soluble polymer is in the range of 10 to 1000 ppm (pure polymer content) relative to the stock solids concentration, and preferably 50 to 500 ppm.
[0034] The retention aid of the present invention, which is a water-in-oil emulsion of an anionic water-soluble polymer, can be added simultaneously with paper strength agents, sizing agents, aluminum sulfate, coagulants, and other papermaking chemicals. Although it may be used in combination with other cationic water-soluble polymers, amphoteric water-soluble polymers, anionic water-soluble polymers, nonionic water-soluble polymers, bentonite, colloidal silica, etc. as a retention aid, its use as a one-liquid retention aid is more advantageous than other retention aid formulations and is therefore preferred. EXAMPLES
[0035] The retention aid comprising a water-in-oil emulsion of an anionic water-soluble polymer according to the present invention and the method for improving the retention of papermaking raw materials using the same will be specifically described below, but the present invention is not limited to the following examples.
[0036] Example 1 As retention aids consisting of water-in-oil emulsions of anionic water-soluble polymers in the present invention, samples 1 to 4 were prepared by a conventional method of water-in-oil emulsion polymerization. Samples 1, 3, and 4 were produced by a conventional method of water-in-oil emulsion polymerization by adding an inorganic salt to the aqueous solution mixed with the monomer mixture during polymerization. Their compositions and physical properties are shown in Table 1.
[0037] Comparative Example 1 Retention aid samples 5 to 9, which are composed of a water-in-oil emulsion of an anionic water-soluble polymer outside the scope of the present invention, were prepared by a conventional water-in-oil emulsion polymerization method. Their compositions and physical properties are shown in Table 1. In addition, commercially available retention aid samples A to C were prepared. Their compositions and physical properties are shown in Table 2.
[0038] (Table 1) TIFF0007619554000002.tif4190Monomer composition; AAC: acrylic acid, AAM: acrylamide Inorganic salt; SC: sodium chloride, inorganic salt addition rate: volume of water-in-oil emulsion Viscosity of 0.2% by mass aqueous solution: Viscosity (mPa s) measured at 25°C when the polymer is dissolved in water to a concentration of 0.2% by mass.
[0039] (Table 2) TIFF0007619554000003.tif2391 Product form: E: Water-in-oil emulsion, D: Dispersion polymerized liquid in salt water Viscosity of 0.2% by mass aqueous solution: Viscosity (mPa s) measured at 25°C when the polymer is dissolved in water to a concentration of 0.2% by mass. Viscosity of 0.5% by mass salt solution: Viscosity (mPa s) measured at 25°C when the polymer is dissolved in 4% by mass salt solution to a concentration of 0.5% by mass.
[0040] (Example 2) (Test assuming addition of shear process) LBKP (hardwood bleached kraft pulp) adjusted to a beating degree of 340 mL was diluted with fresh water, light calcium carbonate was added, and the mixture was used as the adjusted inlet stock for the test. In the test, a Britt-type dynamic jar tester (using 30 mesh wire) was used to measure the total retention rate and ash retention rate. The physical properties of the adjusted stock were 9447 ppm solids concentration, 40 mass% light calcium carbonate and other ash content relative to the stock solids concentration, pH 8.8, and electrical conductivity 21 mS / m. The turbidity of the adjusted stock filtered through Whatman No. 41 filter paper was 87 NTU (using HACH 2100P model), and the cation demand was 0.006 meq / L (using Mutec PCD-05 model). A predetermined amount of adjusted paper stock was collected, and 1.0% by mass of commercially available cationic starch was added (relative to the paper stock solids), and the mixture was stirred at 850 rpm for 20 seconds. Then, 300 ppm (pure polymer content) of a 0.1% by mass aqueous solution of sample 1 in Table 1 was added to the paper stock solids, and the mixture was stirred at 850 rpm for 30 seconds (assuming addition to the screen inlet). The filtrate was collected for a certain period of time and filtered with ADVANTEC No. 2 filter paper, after which the SS was measured and the total retention rate was calculated. The filter paper was incinerated at 525°C for 2 hours to measure the ash retention rate. In addition, the same test was carried out under the same conditions using the same adjusted paper stock, except that after adding sample 1, the mixture was stirred at 850 rpm for 40 seconds (assuming addition to the fan pump inlet). The same test was also carried out for sample 2 in Table 1. These results are shown in Table 3.
[0041] Comparative Example 2 Using the same conditioned paper stock as in Example 2, similar tests were carried out under the same conditions as in Example 2 using Samples 5, 8, and 9 in Table 1 and Sample A in Table 2. The results are shown in Table 3.
[0042] Comparative Example 3 Using the same prepared sample as in Example 2, the same test as in Example 2 was carried out, except that the stirring speed after adding Sample 1 was changed to 850 rpm for 10 seconds (assuming addition to the screen outlet). The same test was carried out for Samples 2, 5, 8, and 9 in Table 1 and Sample A in Table 2. The results are shown in Table 4.
[0043] (Table 3) TIFF0007619554000004.tif3791
[0044] (Table 4) TIFF0007619554000005.tif3367
[0045] In Example 2, which was based on the assumption that the material was added to the screen inlet where shear forces of the papermaking process are applied (mixing time 30 seconds) and the fan pump inlet where it was added (mixing time 40 seconds), the water-in-oil emulsion sample of the anionic water-soluble polymer of the present invention showed a higher retention effect than samples outside the scope of the present invention. Sample 1, which contained an inorganic salt, showed higher retention performance. On the other hand, in Comparative Example 3, which was based on the assumption that the material was added to the screen outlet where no shear forces of the fan pump and screen are applied (mixing time 10 seconds), the difference in effect between the water-in-oil emulsion sample of the anionic water-soluble polymer of the present invention and samples outside the scope of the present invention was small.
[0046] (Example 3) (High-speed papermaking additive test) LBKP adjusted to a beating degree of 340 mL was diluted with fresh water, and light calcium carbonate was added to prepare the adjusted inlet stock for testing. In the test, a Britt-type dynamic jar tester (using 30 mesh wire) was used to measure the total retention rate and ash retention rate. The physical properties of the adjusted stock were 9379 ppm solids concentration, 39 mass% ash content (light calcium carbonate, etc.) relative to the stock solids concentration, pH 8.8, and electrical conductivity 18 mS / m. The turbidity of the adjusted stock filtered through Whatman No. 41 filter paper was 135 NTU (using HACH 2100P model), and the cation demand was 0.012 meq / L (using Mutec PCD-05 model). A certain amount of prepared paper stock was collected, and 1.0% by mass of commercially available cationic starch was added (relative to the paper stock solids), and the mixture was stirred at 1300 rpm for 20 seconds. Then, 300 ppm of a 0.1% by mass aqueous solution of Sample 1 in Table 1 was added (polymer pure content) relative to the paper stock solids, and the mixture was stirred at 1300 rpm for 10 seconds. The filtrate was collected for a certain period of time, filtered with ADVANTEC No. 2 filter paper, and the SS was measured to determine the total retention rate. The filter paper was incinerated at 525°C for 2 hours to measure the ash retention rate. In addition, the same test was conducted under the same conditions using the same prepared paper stock, except that the stirring speed was changed to 1600 rpm. The stirring speed of 1300 rpm of the Britt type dynamic jar tester is estimated to be equivalent to a high-speed papermaking speed of at least 800 m / min, although this depends on the papermaking machine and papermaking conditions. These results are shown in Table 5.
[0047] Comparative Example 4 Using the same conditioned paper stock as in Example 3, a similar test was carried out under the same conditions as in Example 3 using Sample 5 in Table 1. The results are shown in Table 5.
[0048] Comparative Example 5 Using the same conditioned paper stock as in Example 3, the same tests were carried out under the same conditions as in Example 3 using Samples 1 and 5 in Table 1, except that the stirring speed was changed to 700 rpm. The results are shown in Table 6.
[0049] (Table 5) TIFF0007619554000006.tif2291
[0050] (Table 6) TIFF0007619554000007.tif2067
[0051] In Example 3, which simulated the shear force of high-speed papermaking on a papermaking machine, the water-in-oil emulsion sample of the anionic water-soluble polymer of the present invention showed a higher retention effect than samples outside the scope of the present invention. This confirmed that, among polymer samples having the same molar composition and similar molecular weight, polymer samples with a charge encapsulation rate of more than 15.0% showed a high retention effect at high-speed shear.
[0052] (Example 4) (Test to simulate addition of shear process) LBKP adjusted to a beating degree of 365 mL was diluted with fresh water, light calcium carbonate was added, the pH was adjusted, and the adjusted stock was used in the test. In the test, a Britt-type dynamic jar tester (using 30 mesh wire) was used to measure the total retention rate and ash retention rate. The physical properties of the adjusted stock were 9272 ppm solids concentration, 38 mass% ash content (light calcium carbonate, etc.) relative to the stock solids concentration, pH 7.9, and electrical conductivity 48.4 mS / m. The turbidity of the adjusted stock filtered through Whatman No. 41 filter paper was 140 NTU (using HACH 2100P model), and the cation demand was 0.005 meq / L (using Mutec PCD-05 model). A predetermined amount of adjusted stock was collected, and 1.0% by mass of commercially available cationic starch was added (relative to stock solids), and the mixture was stirred at 850 rpm for 20 seconds. Then, 300 ppm of a 0.1% by mass aqueous solution of sample 3 in Table 1 was added (polymer pure content) relative to the stock solids, and the mixture was stirred at 850 rpm for 40 seconds (assuming addition to the fan pump inlet). The filtrate was collected for a certain period of time and filtered with ADVANTEC No. 2 filter paper, after which the SS was measured and the total retention rate was calculated. The filter paper was incinerated at 525°C for 2 hours, and the ash retention rate was measured. In addition, the same test was conducted under the same conditions, except that the stirring time after the addition of sample 3 was changed to 10 seconds (assuming addition to the screen outlet). These results are shown in Table 7.
[0053] Comparative Example 6 Using the same conditioned paper stock as in Example 4, a similar test was carried out under the same conditions as in Example 4 using Sample 6 in Table 1. The results are shown in Table 7.
[0054] (Table 7) TIFF0007619554000008.tif2691
[0055] Compared to the assumed addition at the screen outlet of the papermaking process (mixing time 10 seconds), the assumed addition at the fan pump inlet where shear force is applied (mixing time 40 seconds) showed a higher retention effect in the water-in-oil emulsion sample of the anionic water-soluble polymer of the present invention than in the sample outside the scope of the present invention. This confirmed that, among polymer samples having the same molar composition and molecular weight, polymer samples with a charge encapsulation rate of over 15.0% exhibit a high effect at high shear.
[0056] (Example 5) (Shearing process and high-speed papermaking addition simulation test) LBKP adjusted to a beating degree of 370 mL was diluted with fresh water, light calcium carbonate was added, the pH was adjusted, and the mixture was used as the adjusted inlet stock for the test. In the test, a Britt-type dynamic jar tester (using 30 mesh wire) was used to measure the total retention rate and ash retention rate. The physical properties of the adjusted stock were 9272 ppm solids concentration, 38 mass% ash content (light calcium carbonate, etc.) relative to the stock solids concentration, pH 8.0, and electrical conductivity 48.0 mS / m. The turbidity of the adjusted stock filtered through Whatman No. 41 filter paper was 140 NTU (using HACH's 2100P model), and the cation demand was 0.01 meq / L (using Mutec's PCD-05 model). A certain amount of adjusted paper stock was collected, 1.0% by mass of commercially available cationic starch was added (relative to the paper stock solids), and the mixture was stirred at 1200 rpm for 30 seconds. Then, 300 ppm (polymer pure) of a 0.1% by mass aqueous solution of sample 4 in Table 1 was added to the paper stock solids, and the mixture was stirred at 1200 rpm for 30 seconds (assuming addition to the screen inlet). The filtrate was collected for a certain period of time and filtered with ADVANTEC No. 2 filter paper, after which the SS was measured and the total retention rate was calculated. The filter paper was incinerated at 525°C for 2 hours to measure the ash retention rate. In addition, the same test was conducted under the same conditions using the same adjusted paper stock, except that the stirring time after adding sample 4 was changed to 10 seconds (assuming addition to the screen outlet). These results are shown in Table 8.
[0057] Comparative Example 7 Using the same conditioned paper stock as in Example 5, tests similar to those in Example 5 were carried out using Sample 7 in Table 1 and Samples B and C in Table 2. The results are shown in Table 8.
[0058] (Table 8) TIFF0007619554000009.tif3191
[0059] In the case of assuming addition to the screen outlet of the papermaking process (mixing time 10 seconds), the difference in effectiveness was small compared to samples outside the scope of the present invention, but in the case of assuming addition to the screen inlet where shear force is applied (mixing time 30 seconds), a high retention effect was shown. In addition, it was confirmed that the retention effect of the cationic retention aid sample C was low, and that the anionic retention aid was an effective paper stock.
[0060] (Example 6) (Test assuming addition of shear process) The liner papermaking material for paperboard made by a certain paper manufacturer (solid concentration 13382 ppm, ash content 1842 ppm, pH 6.5, electrical conductivity 192 mS / m) was used for the test. The turbidity of the paper filtrate from Whatman No. 41 filter paper was 66 NTU (using HACH's 2100P model) and the cation demand was 0.021 meq / L (using Mutec's PCD-05 model). In the test, a Britt-type dynamic jar tester (using 30 mesh wire) was used to measure the total retention and ash retention. A 0.1% by mass aqueous solution of Sample 1 in Table 1 was added to the paper stock solids at 200 ppm (polymer pure content), and after stirring for 40 seconds at a stirring speed of 850 rpm (assuming addition to the fan pump inlet), the filtrate was collected for a certain period of time and filtered with ADVANTEC No. 2 filter paper, after which the SS was measured and the total retention was calculated. The filter paper was incinerated at 525°C for 2 hours, and the ash retention was measured. These results are shown in Table 9.
[0061] Comparative Example 8 Using the same papermaking material as in Example 6, the same tests were carried out under the same conditions as in Example 6 using Sample 5 in Table 1. The results are shown in Table 9.
[0062] Comparative Example 9 The same test as in Example 6 was carried out using the same papermaking material as in Example 6, except that the stirring speed after adding Sample 1 was changed to 850 rpm for 10 seconds (assuming addition to the screen outlet). Sample 5 in Table 1 was also similarly tested. The results are shown in Table 10.
[0063] (Table 9) TIFF0007619554000010.tif2684
[0064] (Table 10) TIFF0007619554000011.tif2484
[0065] In an example assuming addition to the inlet of a fan pump where shear forces are applied in the papermaking process (mixing time 40 seconds), a water-in-oil emulsion sample of an anionic water-soluble polymer of the present invention showed a higher retention effect than samples outside the scope of the present invention. On the other hand, in a comparative example assuming addition to the outlet of a screen where shear forces of a fan pump and screen are not applied (mixing time 10 seconds), a sample outside the scope of the present invention showed a higher retention effect than a water-in-oil emulsion sample of an anionic water-soluble polymer of the present invention.
[0066] (Example 7) (Assuming addition of shear process, drainage performance evaluation) LBKP adjusted to a beating degree of 359 mL was diluted with fresh water, and light calcium carbonate was added to prepare the adjusted inlet stock for testing. Drainage performance was evaluated using a dynamic drainage analyzer (DDA, Matsubo). The physical properties of the adjusted stock were 9488 ppm solids, 38.7 mass% light calcium carbonate and other ash content relative to the stock solids, pH 8.5, and electrical conductivity 17.7 mS / m. The turbidity of the adjusted stock filtered through Whatman No. 41 filter paper was 293 NTU (using HACH's 2100P model), and the cation demand was 0.006 meq / L (using Mutec's PCD-05 model). A predetermined amount of the adjusted paper stock was put into a DDA mixing tank with a 62 mesh wire at the bottom. After stirring for 5 seconds at a stirring speed of 1600 rpm, 1.0 mass% of commercially available cationic starch was added (relative to the paper stock solids), and after stirring for 20 seconds, 300 ppm (pure polymer content) of a 0.1 mass% aqueous solution of sample 1 in Table 1 was added relative to the paper stock solids, and after stirring for 50 seconds at a stirring speed of 1600 rpm (assuming addition at the fan pump inlet), the paper stock was sucked under a reduced pressure of 300 mBar, and the drainage time and sheet moisture content at the time when a sheet was formed on the wire were measured. In addition, the same test was conducted under the same conditions using the same adjusted paper stock, except that the stirring time after adding sample 1 was changed to 80 seconds (assuming addition upstream of the papermaking process from the fan pump). These results are shown in Table 11.
[0067] Comparative Example 10 Using the same conditioned paper stock as in Example 7, tests similar to those in Example 7 were carried out using Samples 5 and 8 in Table 1. The results are shown in Table 11.
[0068] Comparative Example 11 The same test as in Example 7 was carried out using the same conditioned paper stock as in Example 7, except that the mixing time after adding Sample 1 was changed to 10 seconds (assuming addition at the screen outlet). Similarly, the test was carried out using Samples 5 and 8 in Table 1. The results are shown in Table 12.
[0069] (Table 11) TIFF0007619554000012.tif2791
[0070] (Table 12) TIFF0007619554000013.tif2367
[0071] In the case of assuming addition at the fan pump inlet where shear forces are applied in the papermaking process (mixing time 50 seconds) and addition upstream of the fan pump in the papermaking process (mixing time 80 seconds), the water-in-oil emulsion sample of the anionic water-soluble polymer of the present invention had a shorter drainage time and a lower sheet moisture content than samples outside the scope of the present invention, confirming that it has excellent drainage performance under conditions of high shear.
[0072] It has been confirmed that the water-in-oil emulsion of an anionic water-soluble polymer of the present invention exhibits excellent retention and drainage performance when added to the inlet, outlet, and screen inlet of a fan pump where shear force is applied in the papermaking process, or when high-speed papermaking is performed. By applying the water-in-oil emulsion of an anionic water-soluble polymer of the present invention as a retention aid under papermaking conditions where high shear is applied, it is possible to achieve improvements in productivity and paper quality.
Claims
1. A retention aid comprising a water-in-oil emulsion of an anionic water-soluble polymer, the water-in-oil emulsion being produced by emulsifying an aqueous monomer mixture solution containing 5 to 80 mol % of a monomer represented by the following general formula (1) and 20 to 95 mol % of a nonionic water-soluble monomer with a surfactant so that a water-immiscible organic liquid constitutes a continuous phase and the aqueous monomer mixture solution constitutes a dispersed phase, adding an azo-based or peroxide-based initiator in an amount of 100 to 500 ppm per monomer, adding an inorganic salt in an amount of 0.5 to 5 mass % based on the amount of the water-in-oil emulsion liquid, polymerizing the resulting mixture, and then adding a phase inversion agent, the anionic water-soluble polymer having a charge inclusion rate of more than 15.0% as measured according to the following definition (A), and an intrinsic viscosity of the anionic water-soluble polymer in a 4 mass % saline solution at 0.5 mass % measured at 25° C. of 15 to 30 dl / g. General formula (1) R 1 is hydrogen, a methyl group or a carboxymethyl group, and Q is SO 3 , C 6 H 4 SO 3 , CONHC (CH 3 ) 2 CH 2 SO 3 , C 6 H 4 COO or COO, R 2 is hydrogen or COOY 2 , Y 1 Or Y 2 represents a hydrogen atom or a cation. Definition (A): Charge inclusion rate (%) = (1-α / β) x 100 α is the titration amount obtained by titrating a 0.0025% by mass aqueous solution of an anionic water-soluble polymer adjusted to pH 10.0 with ammonia with a 1 / 1000N aqueous solution of polydiallyldimethylammonium chloride. β is the titration amount obtained by applying shear to a 0.0025% by mass aqueous solution of an anionic water-soluble polymer adjusted to pH 10.0 with ammonia and titrating it with a 1 / 1000N aqueous solution of polydiallyldimethylammonium chloride.
2. a water-in-oil emulsion of an anionic water-soluble polymer, the water-in-oil emulsion being produced by: emulsifying an aqueous monomer mixture solution containing 5 to 80 mol % of a monomer represented by the following general formula (1) and 20 to 95 mol % of a nonionic water-soluble monomer with a surfactant so that a water-immiscible organic liquid is the continuous phase and the aqueous monomer mixture solution is the dispersed phase; adding an azo-based or peroxide-based initiator at 100 to 500 ppm per monomer; adding an inorganic salt at 0.5 to 5 mass % based on the amount of the water-in-oil emulsion liquid; polymerizing the resulting mixture; and then adding a phase inversion agent; the anionic water-soluble polymer has a charge inclusion rate of more than 15.0% as measured according to definition (A) below, and an intrinsic viscosity of 15 to 30 dl / g in a 4 mass % saline solution at 0.5 mass % of the anionic water-soluble polymer measured at 25° C., the water-in-oil emulsion being characterized in that the water-in-oil emulsion of an anionic water-soluble polymer is added to a papermaking raw material prior to papermaking. General formula (1) R 1 is hydrogen, a methyl group or a carboxymethyl group, and Q is SO 3 , C 6 H 4 SO 3 , CONHC (CH 3 ) 2 CH 2 SO 3 , C 6 H 4 COO or COO, R 2 is hydrogen or COOY 2 , Y 1 Or Y 2 represents a hydrogen atom or a cation. Definition (A): Charge inclusion rate (%) = (1-α / β) x 100 α is the titration amount obtained by titrating a 0.0025% by mass aqueous solution of an anionic water-soluble polymer adjusted to pH 10.0 with ammonia with a 1 / 1000N aqueous solution of polydiallyldimethylammonium chloride. β is the titration amount obtained by applying shear to a 0.0025% by mass aqueous solution of an anionic water-soluble polymer adjusted to pH 10.0 with ammonia and titrating it with a 1 / 1000N aqueous solution of polydiallyldimethylammonium chloride.
3. The method for improving the yield of papermaking raw materials according to claim 2, characterized in that the papermaking raw materials before papermaking to which the water-in-oil emulsion of the anionic water-soluble polymer has been added are passed through one or more shearing processes selected from a fan pump and a screen.
Citation Information
Patent Citations
Anionic copolymers prepared in inverse emulsion matrices and their use in preparing cellulosic fiber compositions
JP2005511831A
Method for dehydrating organic sludge
JP2008221171A
Powdery ionic water-soluble polymer, and use thereof
JP2010159387A
Powdery ionic water-soluble polymer, and use method thereof
JP2013060498A
Method for reducing pitch by anionic water-soluble polymer
JP2015021195A